Pedro Pino: governor of Zuni Pueblo, 1830-1878 - Hart, E. Richard, author; Utah State University Press, publisher (Colorado State University. Libraries, 2003)
Pedro Pino, or Lai-iu-ah-tsai-lu (his Zuni name) was for many years the most important Zuni political leader. He served during a period of tremendous change and challenges for his people. Born in 1788, captured by Navajos in his teens, he was sold into a New Mexican household, where he obtained his Spanish name. When he returned to Zuni, he spoke three languages and brought with him a wealth of knowledge regarding the world outside the pueblo. For decades he ably conducted Zuni foreign relations, defending the pueblo's sovereignty and lands, establishing trade relationships, interacting with foreigners-from prominent military and scientific expeditions to common emigrants-and documenting all in a remarkable archive. Steeped in Zuni traditions, he was known among other things for his diplomatic savvy, as a great warrior, for his oratory, and for his honesty and hospitality. More than a biography, Richard Hart's work provides a history of Zuni during an especially significant period.--Provided by publisher. More than a biography, Richard Hart's work provides a history of Zuni during an especially significant period. Also the author of Zuni and the Courts: A Struggle for Sovereign.
Early Years -- First Years as Governor -- Further Warfare -- Citizenship and the Zuni Land Grant -- "Entangling Alliances" -- The Navajo War -- Expeditions to and from Zuni: "Enough to Pay Them for Going" -- "Our Sheep Is Dying!" -- Reservation and Retirement: "I Have Been a Great Captain" -- Though Your Body Perish -- Afterword -- Appendix A: Biography of Pedro Pino -- Appendix B: Orders No. 41 and Articles of Convention -- Appendix C: Grant Given to Zuni, Year 1689 -- Appendix D: Treaty between the United States of America and Certain Indian Pueblos, or Towns.
Keywords: Zuni Indians -- Kings and rulers -- Biography; Governors -- New Mexico -- Zuni -- Biography; Zuni Indians -- History -- 19th century; Zuni Indians -- Government relations; Zuni (N.M.) -- History -- 19th century; Zuni (N.M.) -- Politics and government; Pino, Pedro